VIP Home Care Services : innovating for employee and client well-being in a low-wage, high-value industry - Kleinsmith, Niela; Koene, Bas, 1966-; Green, Cecilia Anne, 1951-; Wright, Sally, active 2018 (London : Rotterdam School of Management, Erasmus University, 2018)
In 2017, Gwen Jones, founder and owner of VIP Home Care Services, a local UK home care company, began reviewing her company's monthly financial reports, as well as employee recruitment and retention plans for the coming months. Recent legislation and the increasing budget squeeze for social care were constantly challenging Jones's creativity to meet client and employee needs with fewer resources. In 2015, VIP Care had been awarded the local authority's block contract to deliver care in several local towns, which should have placed the company in a strong position in the market. But as budgets and the employee pool shrank, constraints to remain competitive within the home care industry were becoming overwhelming. Jones needed to find a way to maintain high levels of client-focused, quality care while simultaneously supporting, motivating and retaining her employees in an increasingly financially-strapped and competitive industry.
Originally Published InKleinsmith, N., Koene, B., Green, A., & Wright, S. (2018). VIP Home Care Services: Innovating for Employee and Client Well-Being in a Low-Wage, High-Value Industry. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Employee retention -- Case studies; Competition -- Case studies; Personnel management -- Case studies